2006
DOI: 10.1111/j.1600-6143.2006.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Perfusion Reduces the Incidence of Delayed Graft Function in Expanded Criteria Donor Kidney Transplantation

Abstract: The use of expanded criteria donors (ECD) has been proposed to help combat the discrepancy between organ availability and need. ECD kidneys are associated with delayed graft function (DGF) and worse long-term survival. The aim of this study is to evaluate the impact of pulsatile perfusion (PP) on DGF and graft survival in transplanted ECD kidneys. From January 2000 to December 2003, 4618 ECD kidney-alone transplants were reported to the United Network for Organ Sharing. PP was performed on 912 renal allografts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
5
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 30 publications
5
78
5
3
Order By: Relevance
“…The usage of ECD in kidney transplantation was an attempt to counterbalance the organ shortage crisis, and although initial studies reported lower survival after transplantation from ECD than from standard donors, [26][27][28] some recent studies have reported more encouraging results. 29,30 In parallel to these facts occurring in the transplant community, statistics resulting from public health surveillance institutes are all pointing toward a growing prevalence of chronic diseases, such as obesity, diabetes, hypertension, dyslipidemia and coronary artery disease; all of which contribute to an overall worsening health status among the general population, and hence the deceased standard criteria donor pool as well. Our aim was to characterize the trends in comorbidities and physical health attributes of organ donors over more than a decade.…”
Section: Discussionmentioning
confidence: 99%
“…The usage of ECD in kidney transplantation was an attempt to counterbalance the organ shortage crisis, and although initial studies reported lower survival after transplantation from ECD than from standard donors, [26][27][28] some recent studies have reported more encouraging results. 29,30 In parallel to these facts occurring in the transplant community, statistics resulting from public health surveillance institutes are all pointing toward a growing prevalence of chronic diseases, such as obesity, diabetes, hypertension, dyslipidemia and coronary artery disease; all of which contribute to an overall worsening health status among the general population, and hence the deceased standard criteria donor pool as well. Our aim was to characterize the trends in comorbidities and physical health attributes of organ donors over more than a decade.…”
Section: Discussionmentioning
confidence: 99%
“…ГМП широко используется в трансплан-тации почки и доказала эффективность в от-ношении улучшения ранней функции почек и постреперфузионной тканевой концентрации АТФ [11,12].…”
Section: Discussionunclassified
“…As a result, more institutions are using expanded criteria donors (ECD) and deceased after cardiac death donors (DCD), sometimes referred to as marginal donors, to lessen the shortage [16][17][18][19]. The increased utilization of these organs has expanded the donor pool by 30% [19].…”
Section: Overviewmentioning
confidence: 99%
“…The increased utilization of these organs has expanded the donor pool by 30% [19]. Nevertheless, there has been a concomitant increase in the rate of delayed graft function (DGF) and even primary non-function in DCD grafts [16][17][18]. Utilization of these kidneys may contribute to the donor pool, although it is important to maximize the outcomes of these allografts.…”
Section: Overviewmentioning
confidence: 99%